Do contrato de transferência de tecnologia no âmbito da propriedade industrial - Zubcov, Nadja de Alencar Cesar (2012)
The present paper presents a view of the development of commercialized products, the mode of production, the trade development, from the exchanges to effective international transactions; the interference of the State in legal businesses which involve the transfer of technology in the globalized era; and the importance of the removal of the borders. So as to make a complete analysis of the transfer of technology possible, we must necessarily understand the instrument which enables it the contract -, its evolution, its concepts and its requirements. Later, the issue concerning property is discussed, firstly in its classical concept, so that it is possible to compare it to the industrial property, its similarities and discrepancies. Lastly, it is necessary to understand the immaterial object of the contract of technology transfer, what it is and the main ways in which its transfers may occur. The National Institute of Industrial Property, which is responsible for the registration of such contracts, has not been forgotten